Encyclopedia of multimedia technology and networking 2026-02-15T20:47:40+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Pagani, Margherita (Idea Group Reference, 2005)

(untitled)
"This encyclopedia offers a comprehensive knowledge of multimedia information technology from an economic and technological perspective"--Provided by publisher